Copper-iron-molybdenum mixed oxides as efficient oxygen evolution electrocatalysts - Srirapu V.K.V.P.; Sharma C.S.; Awasthi R.; Singh R.N.; Sinha A.S.K. (My University, 2025)
Ternary Cu, Fe and Mo mixed oxides having a nominal compositional formula, CuxFe2-x(MoO4)3 (0 ≤ x ≤ 1.5), have been prepared by a co-precipitation method at pH ≈ 2 and characterized by FT-IR, XRD, XPS, TEM and anodic polarization techniques for use as electrocatalysts for the oxygen evolution reaction (OER) in alkaline solutions. The crystallites of oxides with x ≤ 1 have the monoclinic crystal structure. The OER study shows that replacement of Fe in the Fe2(MoO 4)3 matrix by 0.25-1.0 mol Cu increases the apparent electrocatalytic activity. However, 1.5 mol Cu-addition is detrimental to the OER activity. At E = 1.51 V (vs. RHE) in 1 M KOH, the catalytic activity of the oxide with x = 1 was approximately 50 times the activity of the base oxide (i.e. Fe2(MoO4)3). The Tafel slope of oxides with 0.25 ≤ x ≤ 1.5 ranged between 31 and 37 mV. The reaction order of OH - concentration was nearly unity for oxides with x = 0.25 and 1.5 and it was ∼2 for oxides with x = 0.5, 0.75, and 1.0. Suitable reaction mechanisms consistent with the electrode kinetic parameters have also been proposed. This journal is © the Partner Organisations 2014.